Overexpression of RAB31 in gastric cancer is associated with released exosomes and increased tumor cell invasion and metastasis - Shan Wu; Chaotao Tang; Qing‐wei Zhang; Qian Zhuang; Xin Ye; Jie Xia; Yan Shi; Min Ning; Zhi‐xia Dong; Xin‐jian Wan (Cancer Medicine, 2023)
Abstract Background Gastric cancer (GC) is one of most common cancers worldwide. Several studies have suggested that Rab31 functions as a membrane vesicle transport regulator; however, the mechanism by which RAB31 regulates exosome secretion and promotes metastasis remains to be clarified. Methods We examined the expression of RAB31 protein and mRNA in GC tissue samples via immunohistochemistry and reverse transcription‐polymerase chain reaction assays, respectively. We elucidated the function of RAB31 in GC cells by constructing a cell model and a pulmonary metastatic model of GC with overexpression of RAB31. Protein mass spectrometry was used to identify the exosomal protein. Results RAB31 expression increased at both the protein and mRNA levels with the development of GC. Cells overexpressing RAB31 showed an enhanced ability to migrate in both the in vitro cell model and the pulmonary metastatic model of GC. Exosome nanoparticle tracking analysis and electron microscopy revealed that the both the number and size of the exosomes secreted by GC cells were reduced when RAB31 expression was depleted. Injection of exosomes derived from RAB31 overexpressing cells promoted pulmonary metastasis in vivo. Analysis of the exosomal proteins revealed that PSMA1 was overexpressed in GC tissue in accordance with RAB31 expression. PSMA1 overexpression was highly associated with poor prognosis of GC patients. Conclusion Our findings revealed a key role for RAB31 in GC metastasis through regulation of exosome secretion.